Influence of Low Protein Diet-Induced Fetal Growth Restriction on the Neuroplacental Corticosterone Axis in the Rat - Schmidt, Marius; Rauh, Manfred; Schmid, Matthias C.; Huebner, Hanna; Ruebner, Matthias; Wachtveitl, Rainer; Cordasic, Nada; Rascher, Wolfgang; Menendez-Castro, Carlos; Hartner, Andrea; Fahlbusch, Fabian B. (Frontiers in Endocrinology, 2019)
Objectives: Placental steroid metabolism is linked to the fetal hypothalamus-pituitary-adrenal axis. Intrauterine growth restriction (IUGR) might alter this cross-talk and lead to maternal stress, in turn contributing to the pathogenesis of anxiety-related disorders of the offspring, which might be mediated by fetal overexposure to, or a reduced local enzymatic protection against maternal glucocorticoids. So far, direct evidence of altered levels of circulating/local glucocorticoids is scarce. Liquid chromatography tandem-mass spectrometry (LC-MS/MS) allows quantitative endocrine assessment of blood and tissue. Using a rat model of maternal protein restriction (low protein [LP] vs. normal protein [NP]) to induce IUGR, we analyzed fetal and maternal steroid levels via LC-MS/MS along with the local expression of 11beta-hydroxysteroid-dehydrogenase (Hsd11b). Methods: Pregnant Wistar dams were fed a low protein (8%, LP; IUGR) or an isocaloric normal protein diet (17%, NP; controls). At E18.5, the expression of Hsd11b1 and 2 was determined by RT-PCR in fetal placenta and brain. Steroid profiling of maternal and fetal whole blood, fetal brain and placenta was performed via LC-MS/MS. Results: In animals with LP-induced reduced body (p=0.0002) and placental weights (p<0.05) we did not observe any difference in the expressional Hsd11b1/2-ratio in brain or placenta. Moreover, LP diet did not alter corticosterone (Cort) or 11-dehydrocorticosterone (DH-Cort) levels in dams, while fetal whole blood levels of Cort were significantly lower in the LP group (p=0.0005) and concomitantly in LP brain (p=0.003) and LP placenta (p=0.002). Maternal and fetal progesterone levels (whole blood and tissue) were not influenced by LP diet. Conclusion: Various rat models of intrauterine stress show profound alterations in placental Hsd11b2 gatekeeper function and fetal overexposure to corticosterone. In contrast, LP diet in our model induced IUGR without altering maternal steroid levels or placental enzymatic glucocorticoid barrier function. In fact, IUGR offspring showed significantly reduced levels of circulating and local corticosterone. Thus, our LP model might not represent a genuine model of intrauterine stress. Hypothetically, our observed changes might reflect a fetal attempt to maintain anabolic conditions in the light of protein restriction to sustain regular brain development. This may contribute to fetal origins of later neurodevelopmental sequelae.